search points attachment profile arrow left arrow right star heart verified symbols equation arrow-down question mark check menu accountancyadministrationagriculturalalgebraallarabicartart_musicbelarusbelarus_altbiologybusinesscatalachemistrychineseeconomicsegzamenglishentrepreneurshipenvironmentethicseuskarafirst_aidfrenchgalegogeographygeologygeometrygermangrammarhealthhistoryindia_langindonesian_langinformaticsitalianjapanesekazachkazach_altkoreanlanguagelatinlawlife_scienceliteraturelogicmathematicsmusicnigerian_langother_languagesotherspedagogicsphilosophyphysical_educationphysicspoliticspsychologyreligionrpa_langrussianrussian_altsciencesecurityskillssocial_sciencesociologyspanishstatisticstechnologytourismtrafficukrainianukrainian_altukrainian_literaturewos_civilisation accountancyadministrationagriculturalalgebraall_1arabicartart_music_2belarusbelarus_altbiologybusiness_2catalachemistry_1chineseeconomicsexam_3englishentrepreneurshipenvironment_2ethicseuskarasecurity_1frenchgalegogeography_4geology_4geometrygermangrammarhealthhistoryindia-langindonesian-langinformaticsitalianjapanesekazachAsset 230koreanlanguagelatinlawlife-scienceliteraturelogic_2mathematicsmusicnigerian-langotherlanguagesother_1pedagogicsphilosophyphysical_educationphysicspoliticspsychologyreligion_1rpa-langrussianrussian_altsciencesecurity_3_mskills_1allsocial_science_5_msociologyspanishstatisticstechnologytourismtrafficukrainianukrainian_altukrainian_literaturewos_civilisation

Ответ

Проверено экспертом

Ответ дан
axatar

Ответ:

3

Пошаговое объяснение:

frac{(frac{7}{15}- frac{3}{40}-frac{1}{24}):0,7}{(2,4* frac{1}{3}-3)*frac{5}{11} } *frac{1frac{5}{6}:(frac{3}{4}-1frac{2}{3})}{(frac{4}{9}-frac{5}{12}+0,75)*frac{3}{7} } =3

1)(frac{7}{15}- frac{3}{40}-frac{1}{24}):0,7=frac{7*8-3*3-1*5}{120}:frac{7}{10}= \\=frac{56-9-5}{120}*frac{10}{7}=frac{42}{120}*frac{10}{7}=frac{6}{12}=frac{1}{2}

2)(2,4* frac{1}{3}-3)*frac{5}{11} =(2,4:3-3)*frac{5}{11} =(0,8-3)*frac{5}{11} =\\=-2,2*frac{5}{11}=-frac{22}{10} *frac{5}{11}=-frac{2}{2}=-1

3)1frac{5}{6}:(frac{3}{4}-1frac{2}{3})=frac{11}{6}:(frac{3}{4}-frac{5}{3})=frac{11}{6}:frac{3*3-5*4}{12}=frac{11}{6}:frac{9-20}{12}=\\=frac{11}{6}:frac{-11}{12}=frac{11}{6}*frac{-12}{11}=-2

4)(frac{4}{9}-frac{5}{12}+0,75)*frac{3}{7} =(frac{4*4-5*3}{36}+frac{75}{100})*frac{3}{7} =(frac{16-15}{36}+frac{3}{4})*frac{3}{7} =\\=(frac{1}{36}+frac{3}{4})*frac{3}{7} =frac{1+3*9}{36}*frac{3}{7} =frac{28}{36}*frac{3}{7} =frac{4}{12}=frac{1}{3}

5)frac{frac{1}{2}}{-1} *frac{-2}{frac{1}{3} } =frac{-1}{2} *frac{-2*3}{1} =3

Ответы и объяснения

Не тот ответ, который тебе нужен?